   Symbol

# Calculator search results

Formula
Solve the equation
Answer    Graph
$y = 2 \left ( x - 3 \right )$
$y = 3 x + 5$
$x$Intercept
$\left ( 3 , 0 \right )$
$y$Intercept
$\left ( 0 , - 6 \right )$
$x$Intercept
$\left ( - \dfrac { 5 } { 3 } , 0 \right )$
$y$Intercept
$\left ( 0 , 5 \right )$
$2 \left( x-3 \right) = 3x+5$
$x = - 11$
 Solve a solution to $x$
$\color{#FF6800}{ 2 } \left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \right ) = 3 x + 5$
 Multiply each term in parentheses by $2$
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 3 } \right ) = 3 x + 5$
$2 x + \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 3 } \right ) = 3 x + 5$
 Multiply $2$ and $- 3$
$2 x \color{#FF6800}{ - } \color{#FF6800}{ 6 } = 3 x + 5$
$2 x - 6 = \color{#FF6800}{ 3 } \color{#FF6800}{ x } + 5$
 Move the variable to the left-hand side and change the symbol 
$2 x - 6 \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = 5$
$2 x \color{#FF6800}{ - } \color{#FF6800}{ 6 } - 3 x = 5$
 Move the constant to the right side and change the sign 
$2 x - 3 x = 5 \color{#FF6800}{ + } \color{#FF6800}{ 6 }$
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = 5 + 6$
 Organize the expression 
$\color{#FF6800}{ - } \color{#FF6800}{ x } = 5 + 6$
$- x = \color{#FF6800}{ 5 } \color{#FF6800}{ + } \color{#FF6800}{ 6 }$
 Add $5$ and $6$
$- x = \color{#FF6800}{ 11 }$
$\color{#FF6800}{ - } \color{#FF6800}{ x } = \color{#FF6800}{ 11 }$
 Change the sign of both sides of the equation 
$x = - 11$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture